Perancangan Sistem Point Of Sale Pada Jelly Potter Ciapus Bogor Berbasis Android - Novi Aprian; Reko Syarief Hidayatullah; Siti Julaeha (Unversitas Muhammadiyah Riau, 2022)
Technology can make work more efficient, data collection of product stocks and transactions at Jelly Potter Ciapus Bogor requires good management. Processing of product stock data and transactions still uses manual methods which causes slow processing of unstructured data. Overcoming the problem of slowness and data accuracy, the Point Of Sale system design for Jelly Potter Ciapus Bogor was based on android, software development aims to facilitate the data collection process. The research method used by the author in making this system is Research and Development (R&D) because this method is considered more effective in reviewing ongoing business processes. In the process of collecting data the author uses several methods of data collection, including: field studies and library methods. The design of this system is done by creating a model that explains each activity in detail using the Unified Modeling Language (UML). The results of the research are expected to be better in the data collection process, data storage is neater, and reporting is easily accessible because it is via mobile.